Pemodelan Harga Cabai Indonesia dengan Metode Seasonal ARIMAX - Faris Nasirudin; Abdullah Ahmad dzikrullah (Jurnal Statistika dan Aplikasinya, 2023)
Chili is one of the plants favored by the people of Indonesia because Indonesian cuisine is famous for its spicy taste and spices in every food dish. The rise and fall of chili prices in the market are caused by chili farmers whose production decision-making processes are allegedly not handled and supported by a good production and price forecast. Therefore, analysis is needed to see the forecasting of chili prices in Indonesia in the future. The method that researchers use in forecasting in this study is the SARIMA and SARIMAX methods using the variables of rainfall, inflation, and google trend. The analysis shows that the SARIMAX method is the best model for predicting chili prices with a MAPE value of 6.889% compared to a MAPE SARIMA value of 7.630%.